Forward Brillouin scattering in hollow-core photonic bandgap fibers. (5th February 2016) - Renninger, W H; Shin, H; Behunin, R O; Kharel, P; Kittlaus, E A; Rakich, P T
Abstract: We quantify the strength of stimulated forward Brillouin scattering in hollow-core photonic bandgap fiber through a combination of experiments and multi-physics simulations. Brillouin spectroscopy methods reveal a family of densely spaced Brillouin-active phonon modes below 100 MHz with coupling strengths that approach those of conventional silica fiber. The experimental results are corroborated by multi-physics simulations, revealing that relatively strong optomechanical coupling is mediated by a combination of electrostriction and radiation pressure within the nano-scale silica-air matrix; the nontrivial mechanical properties of this silica-air matrix facilitate the large optomechanical response produced by this system. Simulations also reveal an incredible sensitivity of the Brillouin spectrum to fiber critical dimensions, suggesting opportunity for enhancement or suppression of these interactions. Finally, we relate the measured and calculated couplings to the noise properties of the fiber as the foundation for phase- and polarization-noise estimates in hollow-core fiber. More generally, such Brillouin interactions are an important consideration in both the high and low optical intensity limits.